Konsep Qashas dalam Studi Alqur'an - Juhari, Andi Rezal; Amin Shihab, Muhammad (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This article aims to examine the stories in the Al-Qur'an from the perspective of Al-Qur'an science. Due to space limitations, this article will not discuss in depth the wisdom or lessons contained in each story. However, this article will reveal the general lessons, wisdom, or ibrah from these stories. The results of the study show that the stories in the Koran are often repeated with different emphases and editorials. Around 1,463 verses, or a quarter of the Koran, tell the stories of prophets and historical figures, such as Prophets Moses, Noah, Abraham and Yusuf. These stories are spread across various surahs and are often repeated to emphasize moral and spiritual lessons. Some stories, such as the Prophets Noah and Abraham, are repeated in many letters to connect Muslims with the traditions of previous prophets. The purpose and benefit of Qashash al-Qur'an is to provide lessons and wisdom from the stories of previous people, prophets, and pious people who can guide Muslims and humanity. These stories prove the power of Allah, strengthen the apostleship of the Prophet Muhammad SAW, and strengthen faith and steadfastness in preaching. Qashash al-Qur'an also teaches the creed of monotheism, the importance of knowledge, and provides warnings so as not to fall into error. In addition, these stories provide moral examples and practices that can be applied in everyday life, strengthening the belief that Muslims are a noble people and are given sharia according to their abilities.